Line Balancing Analysis to Optimize Production line of Bushing Rubber Using Theory of Constraints and Heuristics Method with Promodel Simulation at PT. Madya Putera Tehnik - Septiadi, Andrian; Dwi Satya, Ririn Regiana; Wiratmani, Elfitria (TALENTA Publisher, 2023)
The development of manufacturing industry is currently experiencing very rapid development, although the Covid-19 pandemic is still ongoing, this development cannot be inhibited. PT. Madya Putera Tehnik is an industry-engaged automotive part manufacturer that produces bushings. The problem experienced is that the high demand for bushing rubber products makes companies have to optimize the performance of employees and their machines so that targets can be met on time. This study aims to analyze the effectiveness of the production line in the process of making rubber bushings as well as to provide suggestions regarding the balance of the track to increase productivity by using the Theory of Constraints and Heuristic methods. The Theory of Constraints method aims to identify bottlenecks at the outer pipe cutting, rubber roll, rubber clean, and packing work stations that are experiencing problems, and the Heuristic method aims to calculate the balance of the production line. The results obtained from data processing, namely the ranked positional weight and largest candidate rules method have the same results with the number of work stations as many as 14 work stations, track the efficiency of 70%, balance delay of 30%, smoothing index of 66.57, and total exits as many as 1145 units of rubber bushings. It can be interpreted that the two methods have proposed the most optimal trajectory conditions. The company should review the balance of the track and the current production capacity of the company.